Disproportionate impacts of the COVID-19 pandemic on early career researchers and disabled researchers in volcanology - Chim, Man Mei; Maters, Elena C.; Morin, Julie; Kavanagh, Janine L.; Donovan, Amy; Aubry, Thomas J.; Schmidt, Anja (Frontiers in Earth Science, 2023)
The COVID-19 pandemic has brought unprecedented challenges to researchers worldwide, and extensive studies have demonstrated that its impacts since March 2020 have been unequal, including across research discipline, gender, and career status. In 2023, as we navigate the post-pandemic times, questions persist regarding potential disparities and enduring effects faced by volcanology researchers, whose activities range from remote field work to laboratory experiments and numerical modelling. In this study, we explore the multifaceted impacts of the pandemic on volcanology researchers through an online survey distributed globally from January to March 2023. Our survey findings reveal that a considerable fraction of volcanology researchers (44-62%) face longer-term challenges from the pandemic that continue to impact their research, with a notably higher proportion among early career researchers (62%) and researchers with disabilities (76%). In addition, over half (52%) of researchers indicated that they had left or considered leaving academia due to pandemic-related factors. A significantly higher proportion of disabled researchers (56-70%) had left or considered leaving academia compared to researchers without disabilities (42%). Our findings underscore the pandemic’s long-lasting and disproportionate impacts on early career and disabled volcanology researchers. We emphasise the need for concerted efforts by research organisations and funding bodies to mitigate the pandemic's enduring impacts and stress the importance of making conferences accessible to support disabled researchers' participation. As the pandemic's long-lasting impacts ripple across the broader scientific community, the insights from this research can be used for fostering equitable practices and shaping policies beyond volcanology to other research disciplines.